The impact on shelf life of Tulum cheese of modified atmosphere packaging - Demir, Pelin; Ilhak, Osman Irfan; Oksuztepe, Gulsum (United Arab Emirates Univ, 2023)
Tulum cheese is one of the most important conventional fermented dairy products produced in Turkiye. In this study, the effects of modified atmosphere packaging on the microbiological, physicochemical, sensory properties, and shelf life of Tulum cheese were investigated. For this aim, Tulum cheese samples were divided into four groups (B=100% CO2, C =100% N-2, D=70% N-2+30% CO2, E=75% N-2+25% CO2), and the control samples were packaged in the air (A). These samples stored at 4 +/- 1(degrees)C were analyzed for the microbiological, chemical, and sensory on days 0, 30, 60, 90, 120, 150, 180, 210, and 240. TMAB, LLP, lactic streptococcus, lipolytic microorganisms, proteolytic microorganisms, and yeast-mold counts increased while the counts of coliform group bacteria, Enterobacteriaceae, and Staphylococcus aureus continually decreased in all groups during the storage. During the storage period, the E. coli and sulfate-reducing anaerobic bacteria counts were detected below detectable levels (<1.0 log10 CFU/g) in all groups. Other chemical parameter values increased continuously while pH values continually decreased during the storage in all the groups. It was observed that the total sensory scores of the samples decreased continually during the storage period. However, when the scores of the E group were evaluated within themselves, significant differences were obtained. In conclusion, Tulum cheese samples packaged in MAP showed significant changes in quality, and their shelf life was extended.
Keywords: Modified atmosphere packaging; Quality characteristics; Sensory evaluation; Shelf-life extension; Tulum cheese